Criticism of Social, Political, and Religious Problems in Indonesia: A Study on Al-Iklīl fī Ma‘ānī al-Tanzīl by Misbah Bin Zainil Mustafa (1917-1994) - Gusmian, Islah; Abdullah, Mustaffa (Journal of Al-Tamaddun, 2023)
Al-Iklīl fī Ma’ānī al-Tanzīl by Misbah bin Zainil Mustafa is a Qur’anic exegesis that was born from the pesantren tradition and was written during the New Order era under the leadership of President Soeharto. Through his exegesis, Misbah criticized social, political, and religious issues in Indonesia. The issues he highlighted, including how he formed his criticism, and its political as well as scholarly ramifications, are the focus of this study. Using descriptive, historical and explanatory methods, this article presents interesting and important findings. First, Misbah was an Indonesian ulama who started to publicly criticize the New Order regime’s policies and Muslims’ behaviors who were deemed inconsistent with Islamic values. In the midst of a hegemonic and repressive political system, Misbah’s attitude was a high risk and faced with political pressure from the New Order regime. Second, the use of Qur’anic exegesis as a medium for expressing criticism was an unusual move. During the New Order era, various criticisms of the government were raised through the mass media, art performances, literary works, or extra-parliamentary movements on the streets, but Misbah used Qur’anic exegesis as a medium for criticism; an out of the ordinary choice. Finally, from a political standpoint, because of his Al-Iklīl, Misbah was able to escape the political pressures of the hegemonic New Order government, and in term of academic contribution, he was able to establish a new tradition in the history of Qur’anic interpretation in Indonesia.